Meminimalisir Waste Pada Proses Produksi Sarung Tangan di CV. XYZ Menggunakan Lean Manufacture - Fathurrahman Muhammad Hakim; Suseno Suseno (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem that occurs in the company is the waste of time during the production process. The method used is to do value stream mapping, current value stream mapping, process activity mapping, identify and analyze waste defects, overprocessing, and motion using fishbone diagram, and provide improvement proposals using 5W + 1H. The most dominant waste is defects with a weight of 22%, overprocessing 17%, and motion 15%. Based on the processing results using Curent Value Stream Mapping, it is known that the percentage of value-added activities is 53% with a time of 578.82 seconds, non-value added is 34% with a time of 364.21 seconds, neccesary non-value added is 13% with a time of 144.52 seconds. Then after improvements to the layout and the addition of SOPs there was a change in the percentage value of VA activity to 75% with a time of 578.82, NVA to 6% with a time of 39 seconds, and NNVA to 19% with a time of 144.52. From the results of the study, suggestions for improvements to overcome waste are making SOPs that will be attached to the production wall and improving the layout so that the glove production time is more efficient.